Understanding the Impact of Pictorial Health Warnings on Smoking Behavior Among Adolescents - Pandji Winata Nurikhwan; Hadrianti Haji Darise Lasari; Dessy Maulina; Mustafa Mustafa; Abdillah Ahsan; Anis Kamila Saleha; Indra Haryanto Ali (Media Kesehatan Masyarakat Indonesia, 2025)
Smoking behavior remains a health challenge in Indonesian society. Riskesdas data shows an increase in smoking prevalence in adolescent groups. One of the control efforts is the implementation of PHW (Pictorial Health Warnings) on cigarette packs in accordance with Permenkes RI No. 28 of 2013. This study aims to determine the effectiveness of cigarette packs in influencing smoking intention and behavior PHW among adolescents in Tanah Bumbu Regency, Banjarbaru City and Banjarmasin City. The study used a quantitative method with a cross-sectional design. Samples were obtained through an accidental sampling technique, obtaining 315 smoking adolescents and 62 non-smoking adolescents. The instrument was a modified version of the Global Youth Tobacco Survey questionnaire. The analysis used was a linear regression test. The results further showed that 64.5% of respondents who did not smoke stated that their intention was very likely due to fear (89.03%) after seeing the warning and the image of smoking causing lung cancer, hence they did not smoke. Furthermore, there is a relationship between pictorial warnings on cigarette packaging with fear (p-value = 0.0001, r = 0.430) with a positive influence of 16.3%. In adolescent smokers, smoking pictures causing throat cancer 2 caused the most fear (71.3%) and the highest urge to quit smoking (66.48%). There is a relationship between pictorial warnings with fear (p-value = 0.0001, r = 0.195) and smoking cessation intensity (p-value = 0.0001, r = 0.728). The positive effect on fear was 3.5% and smoking cessation intensity was 52.9%.